PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT OSI ELECTRONICS BATAM - Wulandari, Sonya; Wasiman (SCIENTIA JOURNAL, 2022)
Human resources consist of all individuals who play a role in the company. In a company, human resources have an important role because they will be directly involved in the process of achieving targets. This research was carried out with the aim of seeing the influence of motivation, work discipline on employee performance at PT OSI Electronics Batam. This research is descriptive quantitative research with a sample of 100 respondents. The results of the study found that; 1) The work motivation variable (X1) can affect the employee performance variable (Y) seen from the results of the significant value of the X1 variable is 0.152 or > 0.05 and the Tcount value of 1.445 is smaller than the Ttable value of 1.660 this means that the X1 hypothesis is rejected or the variable Motivation has no significant effect on employee performance variables; 2) The work discipline variable (X2) cannot affect the employee performance variable (Y) seen from the results of the significant value of the X2 variable is 0.000 or <0.05 and the Tcount is 7.511 > the Ttable value is 1.660, this means that the X2 hypothesis is accepted or the Discipline variable work has a significant effect on employee performance variables; 3) The variable work motivation (X1) and work discipline (X2) jointly affect the employee performance variable (Y) seen from the results that the significant value obtained is 0.000 (<0.005), so it can be concluded that the variable work motivation, work discipline has a significant effect simultaneously (together) on employee performance variables.